Effectiveness of modified nitrogen fertilizer on soil chemical properties and rice plant growth in the textile industrial area - Sudirja, Rija; Rosniawaty, Santi; Rahayu, Sri Muji; Qurrohman, Budy Frasetya Taufik (Kultivasi, 2023)
The imbalance of nutrients and heavy metal contamination is a challenge in increasing plant growth surround the textile industry area. This study aimed to determine the effectiveness of the dosage of Biologically Agent N Organo Mineral Fertilizer (Biomix-N) as a fertilizer and an ameliorant in paddy soil contaminated with textile liquid waste. This study used a randomized block design of eight treatments with four replications. Parameters observed were soil chemical properties after application of Biomix-N (Na-ex, total N, EC, Cd, and pH), rice plant growth (plant height and tiller number), Cd concentration in the plant, and relative agronomic effectiveness (RAE). Data analysis used analysis of variance, Duncan's test at a 5% level, regression, and correlation analysis. The results showed that Biomix-N 500 kg ha-1 affected the value of EC and total N, while it did not affect Na-ex, Cd, pH and Cd uptake by the paddy plant. Biomix-N fertilization affects the height and number of tillers of rice plants at the age of 70 DAP. Biomix-N fertilization 500 kg ha-1 gave an RAE value of 126-176% compared to the control treatment. The total N content of the soil has a high value of coefficient determinant and correlation (R2= 0.76; R = 0.9) on the growth of rice plants. Applying Biomix-N 500 kg ha-1 equal to 300 kg ha-1 of urea was an effective dose for paddy soil surround the textile industrial area.Keywords: Cadmium, nutrient balance, soil amendment